Growth and physiological of chilli (Capsicum annum Var. Kulai) grown in five different nutrient concentrations by using fertigation system - Herman Ronie (2010., 2010)
Experiment on the effects of different nutrient concentrations to chilli plant starting from EC 0.5, EC 1.0, EC 1.5, EC 2.0 and EC 2.5. Also using 1 type of media where C.D+EFB. To study about growing and yield performance of chilli (Capsicum annuum Var Kulai) by using fertigation system. This experiment was carried out and planted in Ladang 10, University Putra Malaysia. The main objective of this study is to examine growth, development and yield of chilli by using 5 different nutrient concentrations by using fertigation system. To analyze which one of treatment are shown their domination in growth and yield production. Which also to find the matching fertilizer level for growing chilli in fertigation system. Plant nutrient analysis also was analysze especially for N, P, K and Mg elements. A one factorial experiment of five treatments replicated four times was arranged in a Completely Randomized Design (CRD). Data on vegetative, reproductive yield performances, maturity growth and physiological responses were analyzed by the analysis of variance (ANOVA) using the SAS 9.0 programme and the mean were differentiated by using Least Significant Different (LSD at 5%). There was different in plant growth of chillie pepper were observed especially in their plant height, chlorophyll content ana total fruit. The plant with T4 was a higher of plant height compares to the other treatments. The result show a significantly higher plant height in T4 and T5 compared with plant height grown in T1, T2 and T3. Although T5 was a highest of chlorophyll content compares to the other treatments and also as a highest in total fruit production. While T5 also was a highest biomass fresh and dry weight. In term of fruit quality, T1 was a highest quality.
Project paper (B.Hort.Sc.) - Universiti Putra Malaysia, 2010.